2011
DOI: 10.1155/2011/564089
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell Therapy Modulates the Inflammatory Response in Experimental Traumatic Brain Injury

Abstract: Therapy with mesenchymal stem cells (MSCs) has showed to be promising due to its immunomodulatory function. Traumatic brain injury (TBI) triggers immune response and release of inflammatory mediators, mainly cytokines, by glial cells creating a hostile microenvironment for endogenous neural stem cells (NSCs). We investigated the effects of factors secreted by MSCs on NSC in vitro and analyzed cytokines expression in vitro in a TBI model. Our in vitro results show that MSC-secreted factors increase NSC prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
86
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 54 publications
4
86
0
2
Order By: Relevance
“…Neural stem cell (NSC) transplantation has considerable potential as a therapeutic intervention in several central nervous system (CNS) disorders, including Parkinson's disease, Huntington's disease, spinal cord injury, and ischemic and traumatic brain injury (TBI) [1,2,3,4]. NSCs display the ability to self-renew and differentiate into cells of broad neuronal and glial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…Neural stem cell (NSC) transplantation has considerable potential as a therapeutic intervention in several central nervous system (CNS) disorders, including Parkinson's disease, Huntington's disease, spinal cord injury, and ischemic and traumatic brain injury (TBI) [1,2,3,4]. NSCs display the ability to self-renew and differentiate into cells of broad neuronal and glial lineages.…”
Section: Introductionmentioning
confidence: 99%
“…It has gained popularity in the management of various neurological disorders such as ALS, stroke, Alzheimer, spinal cord injury, and TBI [15][16][17][18][19]. Preclinical studies [9][10][11] have used various types of stem cells and different routes of administration in the treatment of TBI. These studies suggest that cell transplantation may improve functional outcomes after TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Stem cells have a unique potential of differentiating and multiplying into mature cells, thus replacing the damaged cells [7,8]. Various preclinical studies have suggested the safety and efficacy of stem cells in TBI [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Although the protocols and medium composition used for culture, proliferation and differentiation of cells derived from SVZ has been used in mice (Galindo et al 2011, Filippo et al 2013), showed to be suitable for guinea pig and, as such, can be thereafter used for this purpose. NSFs were able to proliferate and, upon passages, were capable of generating new NSFs with similar growth and morphological features of the primary ones.…”
Section: Discussionmentioning
confidence: 99%